Progesterone and vitamin D downregulate the activation of the NLRP1/NLRP3 inflammasomes and TLR4-MyD88-NF-κB pathway in monocytes from pregnant women with preeclampsia - Matias, Mariana Leticia [UNESP]; Romao-Veiga, Mariana [UNESP]; Ribeiro, Vanessa Rocha [UNESP]; Nunes, Priscila Rezeck [UNESP]; Gomes, Virginia Juliani [UNESP]; Devides, Amanda Carreira [UNESP]; Borges, Vera Therezinha [UNESP]; Romagnoli, Graziela Goretti; Peracoli, Jose Carlos [UNESP]; Peracoli, Maria Terezinha [UNESP] (Elsevier, 2021)
This study evaluated the in vitro modulatory effect of progesterone (PG) and vitamin D (VD) on NLRP1/NLRP3 inflammasomes and TLR4/NF-κB pathway in monocytes from pregnant women with preeclampsia (PE). Monocytes from 20 preeclamptic and 20 normotensive (NT) pregnant women, and THP-1 cells were cultured with/without hyaluronan (HA), PG, or VD to determine gene and protein expression of TLR4 receptor, phosphorylated NF-κB, IκBα, TLR4, MYD88, NF-κB, NLRP1, NLRP3, caspase-1, IL-1β, IL-18, TNF-α, and IL-10. Higher endogenous activation of inflammatory genes and higher protein expression of TLR4 and NF-κB was detected in monocytes of PE group and decreased after PG or VD treatment. Monocyte from PE stimulated with HA increased while treatment with PG or VD decreased the expression of genes and proteins related to the inflammasomes. THP-1 cells showed a similar immune response profile as monocytes from PE. These results demonstrate that PG and VD play an immunomodulatory role in monocyte activation.
Keywords: Monocytes; NLRP1/NLRP3 inflammasomes; Preeclampsia; Progesterone; Vitamin D